Pengaruh Penerapan PP Nomor 23 Tahun 2018 dan Modernisasi Perpajakan Serta Tingkat Kepatuhan Wajib Pajak UMKM di Kota Bekasi - Nurma Risa; Mayta Rizky Puspita Sari (JRAK: Journal of Accounting Research and Computerized Accounting, 2021)
This study aims to determine the effect of the implementation of PP. 23 in 2018 and tax modernization system on Taxpayer Compliance. This research is a quantitative descriptive study. This research is use questionnaire to collect data and one hundred SME (Small Medium Enterprises) taxpayers in Bekasi as respondent. PLS (Partial Least Square) analysis technique is use for data analysis technique. The results showed that the implementation of PP No. 23 in 2018 and Tax Modernization have a positive and significant effect to Taxpayer Compliance. Future research is expected expand the scope of research and add to other variables and factors.